1997
DOI: 10.1292/jvms.59.1167
|View full text |Cite
|
Sign up to set email alerts
|

Hepatoblastoma in a Dog.

Abstract: ABSTRACT. A hepatoblastoma was found in a 13-year-old female Maltese dog. Histologically, the tumor showed a wide trabecular pattern and was frequently accompanied with vascular lake formation. Tumor cells were positive for cytokeratin and neuron specific enolase, but negative for chromogranin. Electronmicroscopically, tumor cells were accompanied with continuous basement membrane and had poorly developed desmosomes. Sinusoidal endothelia had fenestration and were surrounded by myofibroblast-like cells. To the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
21
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 20 publications
0
21
1
Order By: Relevance
“…1,3,13,15 Hepatoblastomas are categorized as either epithelial or mixed (epithelial/mesenchymal) variants. The recognized epithelial cell types of hepatoblastoma include fetal, embryonal and fetal, macrotrabecular, or anaplastic small cell types.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…1,3,13,15 Hepatoblastomas are categorized as either epithelial or mixed (epithelial/mesenchymal) variants. The recognized epithelial cell types of hepatoblastoma include fetal, embryonal and fetal, macrotrabecular, or anaplastic small cell types.…”
mentioning
confidence: 99%
“…3 Immunohistochemistry and other special stains have been utilized to better characterize hepatoblastomas in both humans and animals. 1,3,5,13,15 However, results can be inconsistent. These staining inconsistencies may be caused by variable epithelial, mesenchymal, and teratoid cell populations, variable intracytoplasmic constituents, such as lipid and glycogen, or cellular anaplasia.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It is, however, in line with the previous observations in human for HCCs with sarcomatoid differentiation [16,21] and HBs [17,25,36] which were positive for neuron-specific enolase (NSE) and S-100 protein. Shiga et al [27] reported a HB in a dog to be positive for NSE, but no neuroendocrine granules were observed on electron microscopic examination. S-100 protein is known to be expressed in many neuroectodermal tissues or neoplasms, as well as various other mesenchymal tissues/tumors [2,9,15,35].…”
Section: Discussionmentioning
confidence: 99%
“…This tumor should be distinguished from hepatoblastoma and metastatic neuroendocrine carcinoma of the pancreas, gallbladder and digestive tract. Tumor cells of hepatoblastomas have argyrophilic granules and are positive for cytokeratin, HepPer-1, α-fetoprotein, NSE and synaptophysin but negative for chromogranin A [2,3,16]. In contrast, neuroendocrine tumors are negative for hepatocyte and α-fetoprotein [5].…”
mentioning
confidence: 99%